Optimizing sowing time and weather conditions for enhanced growth and seed yield of chia (Salvia hispanica L.) in semi-arid regions - CB Harisha; KM Boraiah; PS Basavaraj; Hanamant M. Halli; Ram Narayan Singh; Jagadish Rane; K Sammi Reddy; GR Halagundegowda; Amresh Chaudhary; Arvind Kumar Verma; Y Ravi; Honnappa Asangi; et al. (PeerJ)
Background Climate influenced weather events, especially during the flowering, grain filling, and maturity stages, can adversely influence crop yield and quality. Therefore, understanding how the phenological behaviour and yield potential of new crops such as chia are influenced by weather and sowing dates is crucial for maximizing crop yield. This study aimed to assess the impact of sowing dates on the flowering behaviour, and yield attributes of chia morphotypes, as well as to identify optimal weather conditions for achieving higher yields. Methods The study was conducted during 2021–22 and 2022–23 and consisted of fifteen sowing windows from 1st July to 1st February (at 15 days intervals), with two chia morphotypes (white and black seed) arranged in a replicated split-plot design. Phenological events, flowering characters and seed yield traits were recorded regularly. Weather parameters at the experimental location (Maharashtra, India) were recorded. Results The results revealed that weather conditions such as relative humidity (RH) and rainfall favoured the flowering phenology, yield attributes, and seed yield of chia, whereas maximum temperature (Tmax), bright sunshine hours, and accumulated growing degree days had negative effects. Weather parameters significantly influenced the chia seed yield during the cropping period: RH (positive, R2 = 86.1%), Tmax (negative, R2 = 67.4%), rainfall (positive, R2 = 52.9%), and diurnal temperature range (negative, R2 = 74.9%). Black-seeded chia morphotypes consistently produced higher seed yields (10.8% greater) and better yield-contributing traits compared to white types across various sowing dates. The maximum chia seed yield (811–793.1 kg ha−1) was achieved with sowing dates between August 1st and September 1st in this semi-arid region of India. The performance of chia was good under congenial weather conditions, including relative humidity (∼67–72%), maximum temperature (∼30–31 °C), day length (<12.0 h), rainfall (∼200–350 mm), and accumulated growing degree days (∼1,521–1,891). The present study findings can help identify the best suitable regions for chia cultivation by revealing relationships between the performance of chia morphotypes and weather conditions.